Electronic Spectral Characterization of Pr(III) Systems Involving Some Analytically Important Reagents at pH-3 in Ethyanol Medium-Part-I - Sushma Jain, Mrs.; Verma, R.S.; K. Joshi, G. (Asian Journal of Chemistry, 2010)
An electronic spectral investigation of some analytically important compounds with Pr(III) ion in the form of doped model have been discussed in terms of covalency (β), ludd-Ofelt symmetry parameter (T4/T6), bonding parameter (b1/2) , Slater-Condon parameter (F2, F4, F6), Racah parameter (E1, E2, E3), Lande parameter (ζ4f), percentage reduction in F2 parameter (% rF2) and percentage reduction in ζ4f parameter (% rζ4f). The linear relationship between oscillator strength (P) and vT4/vT6 has been discussed with reference to hypersensitive transition, i.e., 3P2 bands of Pr(III) ion.